OPPORTUNITIES AND THREATS IN THE RECEPTION OF MEDIA BY CHILDREN - Skalski, D. W.; Kowalski, D.; Czarnecki, D.; Graczyk, M.; Orel, I.; Starikov, V. (Rehabilitation and Recreation, 2023)
In order to be able to consider the issue of the importance of the media in the process of socialization and determine, at least approximately, what influence the wide availability of the media may have on the course of this process, an attempt should be made to define the concept of socialization. In order to formulate a general problem concerning this issue, such a procedure seems to be necessary. According to Wincenty Okoń, socialization is an overall, complex of activities that include education and upbringing. These activities are undertaken, in a more or less conscious way, by the society, family, school and social environment. These activities are aimed at making the individual a social being, so their nature is to enable the individual to acquire such qualifications, acquire and internalize such value systems and achieve such personality development that, as a result of this process, the individual can become a full-fledged member of society. The socialization of each individual takes place in a certain educational environment. In the social and pedagogical sciences, the educational environment is usually recognized in terms of the individual it affects.